2019
DOI: 10.1016/j.apmr.2018.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Health-Related Quality of Life in Caregivers of Civilians and Service Members/Veterans With Traumatic Brain Injury: Reliability and Validity Data for the TBI-CareQOL Measurement System

Abstract: Results provide psychometric support for the new TBI-CareQOL item banks. As such, these measures fill a significant gap in the caregiver literature where sensitive PRO measures that capture changes in HRQOL are needed to detect improvements for interventions designed to assist family caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…These findings, in conjunction with previously published findings for other measures within the TBI-CareQOL measurement system (Carlozzi, Hanks, et al, 2019; Carlozzi, Ianni, Lange, et al, 2019; Carlozzi, Ianni, Tulsky, et al, 2019; Carlozzi, Kallen, Brickell, et al, 2019; Carlozzi, Kallen, Hanks, Hanks, et al, 2019; Carlozzi, Kallen, Hanks, Kratz, et al, 2019; Carlozzi, Lange, Boileau, et al, 2019; Carlozzi, Lange, French, et al, 2019; Carlozzi, Lange, Kallen, et al, 2019a, 2019b) provide strong support for the clinical utility of this system’s measures. As such, clinicians and researchers should feel comfortable selecting appropriate TBI-CareQOL measures for use as meaningful endpoints in trials focused on improving outcomes in persons with TBI and their informal family caregivers.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These findings, in conjunction with previously published findings for other measures within the TBI-CareQOL measurement system (Carlozzi, Hanks, et al, 2019; Carlozzi, Ianni, Lange, et al, 2019; Carlozzi, Ianni, Tulsky, et al, 2019; Carlozzi, Kallen, Brickell, et al, 2019; Carlozzi, Kallen, Hanks, Hanks, et al, 2019; Carlozzi, Kallen, Hanks, Kratz, et al, 2019; Carlozzi, Lange, Boileau, et al, 2019; Carlozzi, Lange, French, et al, 2019; Carlozzi, Lange, Kallen, et al, 2019a, 2019b) provide strong support for the clinical utility of this system’s measures. As such, clinicians and researchers should feel comfortable selecting appropriate TBI-CareQOL measures for use as meaningful endpoints in trials focused on improving outcomes in persons with TBI and their informal family caregivers.…”
Section: Discussionsupporting
confidence: 80%
“…Previous publications from the first phase of data collection have highlighted preliminary reliability and validity data for both the SF and simulated CATs (i.e., CATs that were simulated using full item bank administration data) for these new measures using the data collected in the initial calibration sample of caregivers of civilians and SMVs with TBI (Carlozzi, Kallen, Hanks, Hanks, et al, 2019; Carlozzi, Kallen, Hanks, Kratz, et al, 2019; Carlozzi, Kallen, Ianni, Hahn, et al, 2019; Carlozzi, Kallen, Ianni, Hahn, Sander, et al, 2019; Carlozzi, Kallen, Sander, et al, 2019; Carlozzi, Lange, French, et al, 2019). Those previous publications also highlighted the reliability and validity data for several generic measures of HRQOL within the TBI-CareQOL Measurement System; this included measures of mental HRQOL (Patient-Reported Outcomes Measurement Information System [PROMIS] Anger, Anxiety, and Depression; Carlozzi, Hanks, et al, 2019), physical HRQOL (PROMIS Sleep Disturbance and Fatigue; Carlozzi, Ianni, Tulsky, et al, 2019), and social HRQOL (PROMIS Ability to Participate in Social Roles and Activities, Satisfaction with Social Roles and Activities, Social Support, Emotional Support, and Social Isolation; Carlozzi, Ianni, Lange, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This report is complemented by several companion articles that provide a more in-depth examination of each of the domains highlighted in this paper. [39][40][41][42][43][44][45][46]…”
mentioning
confidence: 99%
“…In both studies, good internal consistency was found for Caregiving Burden and Caregiving Relationship Satisfaction but not for Caregiving Ideology and Caregiving Mastery. Ideology and mastery could be improved with further development, best achieved with a structured measurement development methodology per the TBI-CareQOL Measurement System (Carlozzi, Kallen, et al, 2018; Carlozzi, Lange, et al, 2018). Although ideology was dropped by Lawton and colleagues (1989), the same five items commonly represented this construct across all three studies, 4 suggesting its potential usefulness for caregiver research with further development.…”
Section: Discussionmentioning
confidence: 99%